AN ASSESSMENT OF FARMERS’ ATTITUDES TOWARDS CROP DAMAGE BY WILDLIFE AND ITS PREVENTION METHODS IN THE ARID LANDSCAPE OF GUJARAT - DESAI, SHAILESH; TALLURI, HEMALATHA; DHARAIYA, NISHITH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Human-Wildlife Conflict (HWC) is one of the most unavoidable challenges to be faced in the era of rapid development. The reason for the human and wildlife interaction is mainly the sharing of resources and the intervention of humans in the wildlife habitats which has resulted in habitat degradation. The present study was carried out in the arid landscape of Gujarat in order to understand the impact of crop damage by wildlife and to know the perception of locals towards the wildlife. One hundred and fifty (150) successful interviews were conducted from ten villages located on the fringe of the Greater Rann of Kachchh, in Banaskatha district using a structured questionnaire. The results shows that the mean area of land available per household is 10.5 ± 7.8 acre with the mean annual income of $ 460 ± 197. It was calculated that the respondents were at loss of $ 318.5, due to crop damage annually. Besides wildlife, water scarcity and natural calamities are other major constraints to the farmers of this area. Wild boar (Sus scrofa) is reported as the major wild animal responsible for crop damage, followed by blue bull (Boselaphus tragocamelus) and wildass (Equus hemionus khur). As a result, 70% of the respondents reported unwillingness towards coexistence. Farmers here are implementing both traditional and modern preventive measures to control the crop damage. The study revealed that those who have more land are more likely to lean towards modern preventive techniques which have no significant influence by the income of the farmers. The study suggests that fencing of farm and removal of pest species may be act as important measures to mitigate the conflicts in this region. However, provision of adequate and timely compensation by the authorities to the farmers for crop damage may help to generate the benevolence among the locals.